The Dark Side of Solo Female Travel: Negative Encounters with Male Strangers. (1st July 2020) - Su, Chiu-Ping; Wu, Tsung-Chiung
Abstract: Research on solo female travel indicates that women traveling alone in foreign countries are subject to different sociocultural and gender norms, and may bear more fear and constraints both temporally and spatially. Harassment from male strangers exerts considerable influence on women's perception of safety. However, issues of how solo female travelers confront stranger harassment remain untouched in tourism or leisure studies. Based on the perspectives of stranger harassment and cultural encounters, this article explores the experiences and interactions of 17 Taiwanese solo females with male strangers. Results revealed when facing harassment, they opted to neglect, forbear, or blame themselves; hardly had they actively fought back. Adding ramifications to the existing knowledge, this article contributes to the understanding of the theoretical conceptualization of stranger harassment of solo female travelers, and is in due response to the dearth of research in this area.